The Choice of the Financial Year-End: Does It Matter? An International Evidence - Al-Hamadeen, Radhi; Issa, Frances; Hewins, Robin (Jordan Journal of Business Administration, 2024)
This paper examines how specific firm characteristics (size, industry, audit fees and age) and firm performance influence the choice of financial year-end (December vs. non-December). The sample consists of companies from Australia, France, Germany, Japan, the United Kingdom and the United States to tackle issues with international diversity. Both domestic and international regulations for each country are addressed in developing expectations and conclusions. The results of the study show that December is generally becoming less and less ‘popular’ compared to a few years back. The results also revealed that December year-end firms tend to be larger and operate in certain types of industries with some industries preferring to close their books at certain dates, whether a December or a non-December month. As a result, financial-reporting comparability issues may arise if firms depart from the year-end chosen by most similar firms. It is also found that older firms tend to have December as their year-end, while relatively younger firms prefer a non-December year-end. Moreover, firms tend to prefer December as audit fees go up. Finally, firms with better performance are less likely to have December as their fiscal year-end. These findings show the importance of the topic and suggest conducting more research by academics and standard setters.